Булавовусі лускокрилі (Lepidoptera, Papilionoidea) Фастівського району Київської області (Україна) - Yepishin, V. V. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2018)
The results of faunistic research on butterflies carried out at 2011–2018 on the territory of Fastiv District are presented. Thus, 71 species from 50 genera and 6 families are recorded over the years of research. The number of identified species constitutes 56,1% of the fauna of Kyiv Region and 37,2% of the fauna of Ukraine. Three species, Iphiclides podalirius (Linnaeus, 1758), Papilio machaon Linnaeus, 1758 (family Papilionidae) and Hamearis lucina (Linnaeus, 1758) (family Riodinidae), are included in the Red Data Book of Ukraine. Iphiclides podalirius (Linnaeus, 1758) was abundant and frequently recorded during at the last 2 years; about 10 localities are known for this species. Papilio machaon Linnaeus, 1758 was found in six localities of Fastiv District and was frequently recorded every year. Hamearis lucina (Linnaeus, 1758) was found at one locality in 2018 only. Twenty eight species from 21 genera (families Hesperiidae, Pieridae, Papilionidae, Lycaenidae and Nymphalidae) are ubiquitous and were found in more than four localities; 22 species from 20 genera (families Hesperiidae, Pieridae, Lycaenidae and Nymphalidae) were common and found in 2–4 localities; 21 species from 16 genera (families Hesperiidae, Pieridae, Riodinidae, Lycaenidae and Nymphalidae) occured very locally and are known from one locality in the studied region. Moreover, three species: Limenitis populi (Linnaeus, 1758), Aglais urticae (Linnaeus, 1758), Nymphalis polychloros (Linnaeus, 1758) (family Nymphalidae) have not been recorded in Fastiv District for last 40 years; these species are known by the matrial from collections of the second half of last century only.